Subnational Debt Management and Restructuring : Lessons from International Experience - Kahkonen, Satu; Gooptu, Sudarshan (World Bank, Washington, DC, 2016)
In the aftermath of the global financial crisis, policymakers around the world are focusing once again on government debt sustainability. In China, subnational government debt is an important part of total government debt, and therefore deserves the attention that policymakers have paid to the topic. Subnational debt has played an important role in financing China’s impressive infrastructure that is the envy of the world. And subnational debt was instrumental in the economic stimulus that China so effectively staged after the global financial crisis, through which China maintained high levels of economic activity. This e-book starts with a summary and presentation of the Chinese perspective on this subject of subnational debt in session one. Session two introduced some international cases which are highly relevant to the current situation in China. Session three brought these international case studies and experts’ perspectives together to arrive at syntheses that narrowed down key issues which China needs to consider going forward in subnational debt management and restructuring. The roundtable discussion among international and Chinese experts on the way forward for China in session four provided an illuminating discussion of this issue. The author hope that this will inform specific policies that will be formulated to help local governments in China manage their subnational debts.